Strategi Kepala Sekolah dalam Mengawal Perubahan Kurikulum Merdeka - Mar’atusholihah, Fadiya; Yahya, Fata Asyrofi (Progressive Journal of Educational Science, 2025)
Curriculum change is inevitable in an education system that demands readiness and active involvement from teachers. However, the implementation of curriculum change often faces various challenges, especially those related to the readiness of human resources in schools. This study aims to analyze the strategies used by school principals in overseeing curriculum change through efforts to build awareness, willingness, knowledge, skills, and strength among teachers. This study uses a qualitative approach with a case study design. Data collection techniques include in-depth interviews, observation, and documentation, with the main informants being the principal, vice principal in charge of curriculum, and teachers. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that principals implement systematic and sustainable strategies through vision socialization, participatory approaches, training and workshops, academic supervision, and reinforcement through feedback and teacher learning communities. These strategies were able to increase teachers' readiness and commitment in implementing curriculum changes, particularly the Merdeka Curriculum. This study concluded that principal leadership plays a strategic role in ensuring the success and sustainability of curriculum change oversight at the school level.